First wind shear observation in PMSE with the tristatic EISCAT VHF radar. Issue 11 (5th November 2016) - Mann, I.; Häggström, I.; Tjulin, A.; Rostami, S.; Anyairo, C. C.; Dalin, P.
Abstract: The Polar Summer Mesosphere has the lowest temperatures that occur in the entire Earth system. Water ice particles below the optically observable size range participate there in the formation of strong radar echoes (Polar Mesospheric Summer Echoes, PMSE). To study PMSE we carried out observations with the European Incoherent Scatter (EISCAT) VHF and EISCAT UHF radar simultaneously from a site near Tromsø (69.58°N, 19.2272°E) and observed VHF backscattering also with the EISCAT receivers in Kiruna (67.86°N, 20.44°E) and Sodankylä (67.36°N, 26.63°E). This is one of the first tristatic measurements with EISCAT VHF, and we therefore describe the observations and geometry in detail. We present observations made on 26 June 2013 from 7:00 to 13:00 h UT where we found similar PMSE patterns with all three VHF receivers and found signs of wind shear in PMSE. The observations suggest that the PMSE contains sublayers that move in different directions horizontally, and this points to Kelvin‐Helmholtz instability possibly playing a role in PMSE formation. We find no signs of PMSE in the UHF data. The electron densities that we derive from observed incoherent scatter at UHF are at PMSE altitudes close to the noise level but possibly indicate reduced electron densities directly above the PMSE. Key Points: Tristatic observations with EISCAT VHF show for the first time wind shear in PMSE Observed wavy PMSE structure supports models that PMSE form due to Kelvin‐Helmholtz instability caused by wind shear Electron density is for prolonged time reduced directly above PMSE, while it appears not perturbed at PMSE altitude